Optimalisasi Badan Usaha Milik Desa (BUMDes) Melalui Akuntabilitas dan Alokasi Dana Desa di Kecamatan Sumberpucung, Kabupaten Malang - Larasati Pingkan Cahya Hernita; Muslimin Muslimin (IPM2KPE, 2023)
This research aims to determine the influence of effectiveness, accountability and allocation of village funds on the optimization of Village-Owned Enterprises (BUMDes) in Sumberpucung District, Malang Regency. This research method uses quantitative methods using primary data. The data collection method uses a questionnaire distributed to respondents according to the criteria. The research results show that accountability influences the optimization of BUMDes, and the allocation of village funds influences the optimization of BUMDes. Keywords: Accountability, BUMDes, Village Funds, Effectiveness